Cognitive psychology - Gilhooly, K. J.; Lyddy, Fiona M.; Pollick, Frank (New York : McGraw-Hill, 2014)
Based on a multidisciplinary approach, the book encourages students to make the connections between cognition, cognitive neuroscience and behaviour. The book provides an up-to-date, accessible introduction to the subject, showing students the relevance of cognitive psychology through a range of examples, applications and international research. Recent work from neuroscience is integrated throughout the book, and coverage is given to rapidly-developing topics, such as emotion and cognition.
Includes bibliographical references and indexes.
Keywords: Cognitive psychology